2018
DOI: 10.1038/s41598-018-29975-6
|View full text |Cite
|
Sign up to set email alerts
|

Deep brain optical coherence tomography angiography in mice: in vivo, noninvasive imaging of hippocampal formation

Abstract: The hippocampus is associated with memory and navigation, and the rodent hippocampus provides a useful model system for studying neurophysiology such as neural plasticity. Vascular changes at this site are closely related to brain diseases, such as Alzheimer’s disease, dementia, and epilepsy. Vascular imaging around the hippocampus in mice may help to further elucidate the mechanisms underlying these diseases. Optical coherence tomography angiography (OCTA) is an emerging technology that can provide label-free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 21 publications
0
31
0
Order By: Relevance
“…To capture eTC-PCT images, a near-infrared laser beam was used which provides high penetration depth within biological tissue 19 . Higher penetration depth can be achieved using longer excitation wavelength 2,3 . In the case of tumor imaging, the high penetration of 808 nm enables photons to be transmitted into tissue and to be absorbed by the vascular network surrounding the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…To capture eTC-PCT images, a near-infrared laser beam was used which provides high penetration depth within biological tissue 19 . Higher penetration depth can be achieved using longer excitation wavelength 2,3 . In the case of tumor imaging, the high penetration of 808 nm enables photons to be transmitted into tissue and to be absorbed by the vascular network surrounding the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Park et al [151] demonstrated the feasibility of non-invasive deep brain vascular imaging and reported the use of microvascular imaging in the hippocampal formation of mice using a 1.7 μm swept-source OCT system. The imaging results demonstrated that the proposed system can visualize blood flow at different locations of the hippocampus corresponding with deep brain areas.…”
Section: Oct Studies On the Brainmentioning
confidence: 99%
“…The SC light was focused into samples with an achromatic lens having a focal length of 30 mm, and the lateral resolution of the SD-OCT was 29 μm, which is similar to that of 1700-nm OCT reported by another group. 20 Figures 4(a) and 4(b) show en-face OCM and OCT images of a pig thyroid gland at a depth of 0.3 mm from the surface. As shown in the result, because both OCM and OCT have the same optical sectioning capabilities, the image contrast in both OCM and OCT imaging was similar.…”
Section: Tissue Imaging With the Developed Sd-ocmmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18][19] In recently reported 1700-nm SS-OCT, an imaging depth of 2.6 mm was realized in imaging of living mouse brains. 20 In our group, we have been developing high-axial-resolution 1700-nm OCT by using a supercontinuum (SC) fiber laser source. Based on our OCT system, we also realized 3-D high-resolution timedomain (TD) OCM in the 1700-nm spectral band {the center wavelength is 1730 nm and the spectral bandwidth is 380 nm [full-width at half-maximum (FWHM)]}, which enabled lateral and axial resolutions of 1.3 and 2.8 μm (in tissue).…”
Section: Introductionmentioning
confidence: 99%